2013
DOI: 10.1186/1556-276x-8-208
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and variant cellular internalization behavior of water-soluble sulfonated nanographene sheets in liver cancer cells

Abstract: Highly exfoliated sulfonated graphene sheets (SGSs), an alternative to graphene oxide and graphene derivatives, were synthesized, characterized, and applied to liver cancer cells in vitro. Cytotoxicity profiles were obtained using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide, WST-1[2-(4-iodophenyl)-3-(4-nitrophenyl)-5-(2,4-disulfophenyl)-2H-tetrazolium, and lactate dehydrogenase release colorimetric assays. These particles were found to be non-toxic across the concentration range of 0.1 to 10 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
(40 reference statements)
1
7
1
Order By: Relevance
“…However, a slight decrease in cell viability is observed in nanohybrid with higher percentage graphene (PU-SN4) indicating some cytotoxic property. Corr et al studied the effect of the sulfonated graphene on Hep3B cell lines and reported drastic decrease of cell viability up to 20% at 100 μg/mL concentration and complete necrosis of cells at 72 h and considered higher insolubility of formazan in the presence of sulfonated graphene as the reason behind it . However, our studies indicate nanohybrid with 4 wt % of sulfonated graphene (i.e.…”
Section: Results and Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…However, a slight decrease in cell viability is observed in nanohybrid with higher percentage graphene (PU-SN4) indicating some cytotoxic property. Corr et al studied the effect of the sulfonated graphene on Hep3B cell lines and reported drastic decrease of cell viability up to 20% at 100 μg/mL concentration and complete necrosis of cells at 72 h and considered higher insolubility of formazan in the presence of sulfonated graphene as the reason behind it . However, our studies indicate nanohybrid with 4 wt % of sulfonated graphene (i.e.…”
Section: Results and Discussioncontrasting
confidence: 68%
“…Corr et al studied the effect of the sulfonated graphene on Hep3B cell lines and reported drastic decrease of cell viability up to 20% at 100 μg/mL concentration and complete necrosis of cells at 72 h and considered higher insolubility of formazan in the presence of sulfonated graphene as the reason behind it. 36 However, our studies indicate nanohybrid with 4 wt % of sulfonated graphene (i.e. ∼331 μg/mL; three times the concentration reported earlier) but still showing the 60% cell viability after 5 days interval suggesting that grafting of the biocompatible polyurethane chains over sulfonated graphene sheet through amine moiety induced sufficient biocompatibility in nanohybrids as compared pure functionalized graphene.…”
Section: Acs Biomaterials Science and Engineeringmentioning
confidence: 44%
See 1 more Smart Citation
“…Cellular uptake and metal internalization through the lipid bilayer are not yet understood well because these layers are made to actively resist any foreign element to pass through the cellular wall. However, numerous reports indicate that surface functionalization of the nanomaterials with hydrophilic or hydrophobic or mixed ligands can aid in the penetration by the one or combination of the following mechanism . (1) Nanostructures can penetrate the plasma membrane of the cell by generating transient holes.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrophobic primitive graphene aggregated on the cell membrane at high concentrations, destroying cytoskeleton arrangement and deforming cells, while hydrophilic G-COOH at low concentrations was highly internalized and did not seem to affect cell functions [ 16 ]. Curley et al [ 48 ] found that sulfonated GO was non-toxic within the concentration range of 0.1–10 mg/mL. Modifications such as carboxylation and dextran conjugate have also been shown to reduce the cytotoxicity of graphene by increasing the hydrophilicity of graphene derivatives [ 49 ].…”
Section: Biocompatibility Of Gbnsmentioning
confidence: 99%